2021
DOI: 10.1002/cssc.202102546
|View full text |Cite
|
Sign up to set email alerts
|

Design of Non‐Incendive High‐Voltage Liquid Electrolyte Formulation for Safe Lithium‐Ion Batteries

Abstract: Battery safety has an ever-increasing significance and is required for consumer's safety. The high flammability of traditional organic liquid electrolyte, which consists of ethylene carbonate and highly flammable linear carbonate, is one of the major reasons for thermal runaway and battery fire events. Replacement of flammable liquid electrolyte with non-incendive one is urgently needed for safe lithium-ion batteries. A fluorinated linear sulfate paired with 1 m LiPF 6 was developed and evaluated as a solvent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…As displayed in Figure c,d, in the electrolyte with and without TMSTFA, NCM811 materials undergo similar electrochemical reactions along with the multiphase transition of H1 + M, M + H2, and H2 + H3 (where H and M represent the hexagonal and monoclinic phases, respectively), corresponding to three pairs of redox peaks at 3.7, 4.0, and 4.2 V, respectively . However, at the 1st cycle, the potential interval (Δ V ) for the H1 + M phase transition in the TMSTFA-added electrolyte is only 0.38 V, while it is as high as 0.74 V in the baseline electrolyte.…”
Section: Resultsmentioning
confidence: 85%
“…As displayed in Figure c,d, in the electrolyte with and without TMSTFA, NCM811 materials undergo similar electrochemical reactions along with the multiphase transition of H1 + M, M + H2, and H2 + H3 (where H and M represent the hexagonal and monoclinic phases, respectively), corresponding to three pairs of redox peaks at 3.7, 4.0, and 4.2 V, respectively . However, at the 1st cycle, the potential interval (Δ V ) for the H1 + M phase transition in the TMSTFA-added electrolyte is only 0.38 V, while it is as high as 0.74 V in the baseline electrolyte.…”
Section: Resultsmentioning
confidence: 85%
“…Clearly, three redox peak pairs at 3.9, 4.0, and 4.2 V are detected, respectively, representing the phase inversion of H1+M, M +H2, and H2+H3 (H and M are hexagonal and monoclinic phases, respectively) of the NCM811 material. 40 With the PFTF additive, the potential difference (ΔV) of the H1+M phase is 0.18 V in the initial cycle (Figure 2d), which is lower than 0.24 V in the blank electrolyte. It is suggested that the PFTF-derived CEI film possesses a rapid Li + transport rate.…”
Section: Resultsmentioning
confidence: 92%
“…In addition, the impact of PFTF on the procedure of Li + intercalation/deintercalation is investigated by analyzing the CV curves of Li/NCM811 batteries (Figure d,e). Clearly, three redox peak pairs at 3.9, 4.0, and 4.2 V are detected, respectively, representing the phase inversion of H1+M, M+H2, and H2+H3 (H and M are hexagonal and monoclinic phases, respectively) of the NCM811 material . With the PFTF additive, the potential difference (Δ V ) of the H1+M phase is 0.18 V in the initial cycle (Figure d), which is lower than 0.24 V in the blank electrolyte.…”
Section: Resultsmentioning
confidence: 96%
“…In both the first (first) and second (second) cycles, three sets of redox couples at 3.9, 4.0, and 4.2 V, respectively, which reflect phase inversion between H1+M, M+H2, and H2+H3, are present in cells with various electrolytes (hexagonal and monoclinic phases are H and M, respectively). 44 Notedly, when the H1+M phase inversion occurs in the first cycle, the potential difference (ΔV) is 0.305 V in the HFM-added electrolyte lower than 0.528 V in the baseline, indicating that HFM additive helps to improve Li + reaction reversibility during the initial Li + de/intercalation process. At the second cycle, a significantly decreased ΔV of 0.041 V in the HFM-containing electrolyte can be observed and it is also much lower than that in the reference (0.144 V).…”
Section: Resultsmentioning
confidence: 99%
“…Examining how HFM affects the kinetic behaviors during the Li + delithiation/intercalation process, the CV measurements are conducted on Li/NCM811 batteries with and without HFM (Figure d,e). In both the first (first) and second (second) cycles, three sets of redox couples at 3.9, 4.0, and 4.2 V, respectively, which reflect phase inversion between H1+M, M+H2, and H2+H3, are present in cells with various electrolytes (hexagonal and monoclinic phases are H and M, respectively) . Notedly, when the H1+M phase inversion occurs in the first cycle, the potential difference (Δ V ) is 0.305 V in the HFM-added electrolyte lower than 0.528 V in the baseline, indicating that HFM additive helps to improve Li + reaction reversibility during the initial Li + de/intercalation process.…”
Section: Resultsmentioning
confidence: 99%